Anna E. Dickinson papers - Dickinson, Anna E. (Anna Elizabeth), 1842-1932.
Correspondence, speeches, writings, plays, legal files, financial papers, newspaper clippings, itineraries, scrapbooks, obituaries, printed material, and other papers relating to Dickinson's activities on behalf of abolition, women's rights, and suffrage and to her career in the theater. Also includes research notes for Dickinson's 1951 biography, Embattled Maiden; The Life of Anna Dickinson, by Giraud Chester.
Topics include the national elections of 1872 and 1888; Dickinson's 1872 campaign work for Horace Greeley; her travel throughout the U.S. while on lecture and campaign circuits; the Republican Party; her 1891 confinement at the State Hospital for the Insane, Danville, Pa., and her lawsuits for damages incurred by the confinement; the Civil War; Reconstruction; social reform in the post-Civil War South; and education.
Family correspondents include her mother, Mary Dickinson, and her sister, Susan Dickinson. Other correspondents include William B. Allison, Susan B. Anthony, Henry Ward Beecher, Samuel Bowles, Noah Brooks, Benjamin F. Butler, Fanny Davenport, Frederick Douglass, Ellen Everett, William Lloyd Garrison, Thomas Wentworth Higginson, Isabella Beecher Hooker, Wendell Phillips, Samuel C. Pomeroy, Whitelaw Reid, Carl Schurz, Theodore Tilton, Mark Twain, Charles Dudley Warner, and John Greenleaf Whittier.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Lecturer, reformer, actress, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allison, William B. -- 1829-1908 -- Correspondence; Anthony, Susan B. -- 1820-1906 -- Correspondence; Beecher, Henry Ward, -- 1813-1887 -- Correspondence; Bowles, Samuel, -- 1826-1878 -- Correspondence; Brooks, Noah, -- 1830-1903 -- Correspondence; Butler, Benjamin F. -- 1818-1893 -- Correspondence; Chester, Giraud, -- 1922-; Davenport, Fanny, -- 1850-1898 -- Correspondence; Dickinson, Mary -- Correspondence; Dickinson, Susan -- Correspondence; Douglass, Frederick, -- 1818-1895 -- Correspondence; Everett, Ellen -- Correspondence; Garrison, William Lloyd, -- 1805-1879 -- Correspondence; Greeley, Horace, -- 1811-1872.; Higginson, Thomas Wentworth, -- 1823-1911 -- Correspondence; Hooker, Isabella Beecher, -- 1822-1907 -- Correspondence; Phillips, Wendell, -- 1811-1884 -- Correspondence; Pomeroy, S. C. -- 1816-1891 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Schurz, Carl, -- 1829-1906 -- Correspondence; Tilton, Theodore, -- 1835-1907 -- Correspondence; Twain, Mark, -- 1835-1910 -- Correspondence; Warner, Charles Dudley, -- 1829-1900 -- Correspondence; Whittier, John Greenleaf, -- 1807-1892 -- Correspondence; Dickinson family -- Correspondence; Republican Party (U.S. : 1854- ); State Hospital for the Insane (Danville, Pa.); Antislavery movements -- United States; Education -- United States; Elections -- United States -- 1872.; Elections -- United States -- 1888.; Mentally ill -- Commitment and detention -- United States; Presidents -- United States -- Election -- 1872.; Presidents -- United States -- Election -- 1888.; Psychiatric hospitals -- Pennsylvania -- Danville; Reconstruction (U.S. history, 1865-1877); Slavery -- United States; Theater -- United States; Women -- Suffrage -- United States; Women's rights -- United States; United States -- Description and travel; United States -- History -- Civil War, 1861-1865.; Actresses; Authors; Lecturers; Reformers